Spatiotemporal discrepancies and risk assessment of toxic heavy metals in surface water of Shitalakhya River around Narayanganj port in Bangladesh - Shahrina Sultana; Md. Sirajul Islam; Md. Humayun Kabir; Rima Sarker; Tanmoy Roy Tusher; Mir Md. Mozammal Hoque; Nowara Tamanna Meghla (International Journal of Agricultural Research, Innovation and Technology)
The urban rivers of developing countries like Bangladesh have been severely affected by toxic heavy metal pollution, posing serious ecological and human health risks. This study aimed to investigate the concentrations, spatiotemporal discrepancies, and associated risks of five alarming toxic metals (Pb, Cd, Cr, Cu and Mn) in the surface water of urban Shitalakhya River around Narayanganj port, one of the biggest and most important river ports in Bangladesh. Water samples were collected for three prevailing seasons i.e., pre-monsoon, monsoon, and post-monsoon from five selected sites. Physicochemical properties (color, odor, temperature, DO, pH, EC and TDS) of river water were also assessed, while heavy metal pollution index (HPI), heavy metal evaluation index (HEI) and degree of contamination (CD) were calculated to evaluate the risks associated with toxic metal pollution in river water. The findings revealed that several physicochemical parameters, especially DO, EC and TDS, were not within the standards. The hierarchy of mean heavy metal concentrations in Shitalakhya River water was found as Mn>Cr>Cu>Cd>Pb during pre-monsoon, Mn>Cu>Cr>Cd>Pb during monsoon, and Mn>Cr>Cu>Pb>Cd during post-monsoon season. The metal concentrations were found to be higher in pre-monsoon and post-monsoon seasons, whereas the concentrations of all the heavy metals excluding Mn were within the standards recommended for domestic use, surface water, fisheries and irrigation purposes. The comparative analysis exhibited that the water quality of Shitalakhya River is deteriorating day by day at an alarming rate. HPI showed a critical pollution index value (drinking) for all three seasons, whereas HEI revealed low heavy metal contamination for all sampling stations. The values of CD indicated a high level of contamination in pre-monsoon and post-monsoon but monsoon season. The results confirmed the spatiotemporal discrepancies in toxic metal concentrations and associated ecological and human health risks, possibly resulting from the hydrological and anthropogenic interventions not only associated with port activities. Hence, urgent collective effort and proper monitoring are of utmost importance to safeguard the public health and this urban riverine ecosystem.